BUSINESS AND ACCOUNTING ASPECTS MENTORING INSIGHT BETWEEN STUDENTS AND MENTORS IN ENTREPRENEURSHIP CONTEXT - Gunawan, Lenny; Efrata, Tommy Christian; Bartle, James (Universitas Brawijaya, Indonesia, 2018)
The research aims toexplore mentor dan mentee's insights toward business and accounting teaching and learning model in entrepreneurship context which able to create a creative business. The research subject is business and accounting teaching and learning model in Universitas Ciputra's Management Study Program, which is applied to project based and using mentoring approach. Informants are facilitators and students who are building start-up businesses. The research uses a qualitative method and case study approach. Results show that Students gain positive insight into business and accounting teaching and learning method that is applied, Facilitators applied the creative method to reach the optimal teaching and learning result, and engagement pattern in form of mentoring is agreed by both parties. These research results are wished to be used for higher education who is working on their entrepreneurship teaching and learning pattern aiming for creating creative businesses.